KEDAULATAN ENERGI NASIONAL: PENGUATAN PERAN NEGARA BERDAULAT & PEMBERDAYAAN SUMBER DAYA INSANI - Ucuk Darusalam; Iskandar Fitri (Jurnal Ilmu dan Budaya, 2016)
There has been lacking of sovereignty of energy in Indonesia as a logical consequence of the state’s ineffectiveness to uphold the mandate promulgated by the 1945 Constitution. The country has been trapped in global capitalism resulting in the weakening position of Indonesia, and eventually weakening political economic and technological power of both state and the society. It brings with it negative impacts on empowerment of human resources that should otherwise develop expertise in coping with the current development of science and technology. The inflow of foreign investment has not made the state strong enough to pave the way for self help to assure welfare of the vast people. This paper is an account of assessing this issue of weak state of Indonesia to enable stronger position in sovereignty of energy and the assurance of human resources development in science and technology.